2007
DOI: 10.1128/jcm.00894-07
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Human Immunodeficiency Virus Rapid Test Evaluation in a Low-Prevalence Ugandan Blood Bank Population

Abstract: The use of rapid tests for human immunodeficiency virus (HIV) has become standard in HIV testing algorithms employed in resource-limited settings. We report an extensive HIV rapid test validation study conducted among Ugandan blood bank donors at low risk for HIV infection. The operational characteristics of four readily available commercial HIV rapid test kits were first determined with 940 donor samples and were used to select a serial testing algorithm. Uni-Gold Recombigen HIV was used as the screening test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 14 publications
8
24
1
1
Order By: Relevance
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies reported clerical errors [8,11,26,28,29,31,34,35,45,50,63–65,67,73,75]. Errors included poor record-keeping [35], data reporting problems, labelling and transcription mistakes [73] and specimen mix-ups.…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 testing was performed on all participants as previously described (16). Briefly, HIV-1 enzyme-linked immunosorbent assay (ELISA) screening was performed using a Genetic Systems rLAV (Bio-Rad Laboratories, Redmond, WA) ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of specificity of the Determine HIV-1/2 assay with specimens from Uganda has been reported previously (6,12,22). We hypothesize that in Kampala, Uganda, in particular, participants had undiagnosed endemic non-HIV infections or circulating substances in their blood that may have cross-reacted with the Determine HIV-1/2 test (12).…”
Section: Discussionmentioning
confidence: 99%